Edukasi Pengetahuan Anemia Dan Obat Tablet Tambah Darah (TTD) Untuk Remaja Putri: Education on Anemia Knowledge and Blood Supplement Tablet Medication (TTD) for Young Women (Jurnal Mitra Masyarakat (JMM), 2024)
Anemia in adolescent girls, with hemoglobin levels <12 g/dL, can affect growth, development and daily activities. The counseling at SMPIT Islamia aims to determine the effect of education on knowledge of anemia and Blood Supplement Tablets (TTD) in young women. This activity involves providing TTD and vitamin C drinks and using the lecture method using leaflets, posters and Spin AneC. The research was conducted with a cross-sectional design and analyzed using the Paired T-test with SPSS. The results show that all counseling methods are effective in increasing knowledge about anemia in adolescent girls, with a p value <0.05.